Improving Willingness to Try Fruits and Vegetables Among Low-Income Children Through Use of Characters (Mary Ann Liebert, 2020)
Purpose: Low-income children are disproportionately affected by high rates of food insecurity and obesity, placing them at risk for poor health outcomes. Diets that are rich in fruits and vegetables (FV) are associated with health benefits such as reducing the risk of obesity. Despite these benefits, American children do not consume nationally recommended amounts of fruits (63%) and vegetables (90%) per day. Data reveal that young children exhibit increased food neophobia toward vegetables. One way to decrease food neophobia is to introduce FV to young children via recipe tasting. The purpose of the study was to increase willingness to try FV among low-income children using live characters at Summer Food Service Program Sites. Methods: The study design was a small-scale pilot study to conduct taste tests of recipes with 125 low-income children. Researchers created recipe-tasting stations at two different sites. At Site 1, characters promoting FV characters were present at the recipe-tasting station. At Site 2, researchers presented recipes without characters being present. Taste tests were conducted once per week for a period of 4 weeks using two previously validated instruments, Taste Test Tool and the Taste and Rate Questionnaire. Results: Results demonstrated that introducing FV recipes with characters showed a trend toward increasing willingness to try FV among low-income children. Data also suggested that low-income children had limited exposure to specific FV before recipe tastings. Conclusion: The use of characters is a promising approach to increase willingness to try FV among low-income children.